Novel In vitro Procedures for Rearing a Root-Feeding Pest (Heteronychus arator) of Grasslands - Hiltpold, Ivan; Moore, Ben D.; Johnson, Scott N. (Frontiers in Plant Science, 2016)
Optimising plant protection against insect herbivory relies on testing plant defence mechanisms and how the insect response to these defensive strategies. Such experiments benefit from using insects generated from standardised rearing protocols since this reduces stochastic variation. Such protocols can be challenging to devise, however, especially for root herbivores. These insects generally have complex and long life cycles, which are often only poorly described. Moreover, using field-captured root herbivores is often suboptimal because it involves extensive excavation from sites selected by chance (their location is not obvious) and larval stages are frequently indistinguishable beyond the family level. We investigated in vitro procedures to improve the availability of the African Black Beetle (ABB) Heteronychus arator, an invasive alien pest in both Australia and New Zealand. Native to Africa, this scarab beetle has established in Australian and New Zealand grasslands, pastures, and crops. Adults feed on the stem of young plants just beneath the soil surface. During the mating season, gravid females lay eggs in the soil, giving rise to larvae feeding on grass roots, causing severe damage, and impairing plant growth. Here, we propose laboratory approaches to collect eggs from field-captured adult beetles, to hatch eggs, and to rear neonate larvae to adults. We propose that these methods will provide plant scientists and entomologists with a better and more controlled supply of ABB larvae for laboratory and field assays. In turn, this will assist with the collection of important information for the management of this insect pest and enhanced protection of plants in crop and grassland ecosystems.